Analysis Crystal Structure and Magnetic Properties of Strontium Ferrite (SrO6Fe2O3) Made Using Powder Metallurg - Hery Adrial; Djuhana Djuhana; Mulyadi Mulyadi; Sunardi Sunardi (Prodi Teknik Mesin, 2023)
Strontium ferrite in this study was obtained from a mixture of strontium carbonate and pure iron sand using the metarlurgi powder method. Variation in the composition of the composition of 1: 5 mol, 1: 6 mol, 1: 7 mol with a total mass of 30 grams, both of raw materials were milled by using a rotary ball mill with an additional 125 ml of distilled water for 6 hours. Then dried using the oven to become powder again. After that the sample was calcined by using a furnace at temperatures about 1000 ℃ and hold for 2 hours The sample was measured by using X-Ray Difraction (XRD) test to determine the crystal structure and the Vibrating Sample Magnetometer (VSM) test to determine the magnetic properties. Samples with a stoichiometric composition with mole ratio SrO: Fe2O3 = 1: 6 have the highest magnetic properties, namely with a remanence value = 48 emu / g or 0.3 Tesla and a coercivity of 2500 Oe. As well as the crystal structure obtained single phase SrO6Fe2O3 (SrFe12O19).